Soil carbon dioxide and nitrous oxide emissions during the growing season from temperate maize‐soybean intercrops - Dyer, Lisa; Oelbermann, Maren; Echarte, Laura (Wiley, 2019)
The Argentine Pampa is one of the major global regions for the production of maize (Zea mays L.) and soybean (Glycine max L. [Merr.]), but intense management practices have led to soil degradation and amplified greenhouse‐gas (GHG) emissions. This paper presents preliminary data on the effect of maize‐soybean intercrops compared with maize and soybean sole crops on the short‐term emission rates of CO2 and N2O and its relationship to soil moisture or temperature over two field seasons. Soil organic carbon (SOC) concentrations were significantly greater (p < 0.05) in the maize sole crop and intercrops, whereas soil bulk density was significantly lower in the intercrops. Soil CO2 emission rates were significantly greater in the maize sole crop but did not differ significantly for N2O emissions. Over two field seasons, both trace gases showed a general trend of greater emission rates in the maize sole crop followed by the soybean sole crop and were lowest in the intercrops. Linear regression between soil GHG (CO2 and N2O) emission rates and soil temperature or volumetric soil moisture were not significant except in the 1:2 intercrop where a significant relationship was observed between N2O emissions and soil temperature in the first field season and between N2O and volumetric soil moisture in the second field season. Our results demonstrated that intercropping in the Argentine Pampa may be a more sustainable agroecosystem land‐management practice with respect to GHG emissions.